A novel secretagogin/ATF4 pathway is involved in oxidized LDL-induced endoplasmic reticulum stress and islet β-cell apoptosis. (8th December 2020) - Wu, Li; Lv, Yuncheng; Lv, Ying; Xiang, Sunmin; Zhao, Zhibo; Tang, Ziqing; Ou, Linling; Yan, Bin; Xiao, Xinhua; Wen, Gebo; Cao, Renxian; Yang, Jing
Abstract: Excessive accumulation of cholesterol in β cells initiates endoplasmic reticulum (ER) stress and associated apoptosis. We have reported that excessive uptake of cholesterol by MIN6 cells decreases the expression of secretagogin (SCGN) and then attenuates insulin secretion. Here, we aimed to determine whether cholesterol-induced SCGN decrease is involved in the modulation of ER stress and apoptosis in pancreatic β cells. In this study, MIN6 cells were treated with oxidized low-density lipoprotein (ox-LDL) for 24 h, and then intracellular lipid droplets and cell apoptosis were quantified, and SCGN and ER stress markers were identified by western blot analysis. Furthermore, small interfer RNA (siRNA)-mediated SCGN knockdown and recombinant plasmid-mediated SCGN restoration experiments were performed to confirm the role of SCGN in ER stress and associated cell apoptosis. Finally, the interaction of SCGN with ATF4 was computationally predicted and then validated by a co-immunoprecipitation assay. We found that ox-LDL treatment increased the levels of ER stress markers, such as phosphorylated protein kinase-like endoplasmic reticulum kinase, phosphorylated eukaryotic initiation factor 2 alpha, activating transcription factor 4 (ATF4), and transcription factor CCAAT-enhancer-binding protein homologous protein, and promoted MIN6 cell apoptosis; in addition, the expression of SCGN was downregulated. siRNA-mediated SCGN knockdown exacerbated β-cell ER stress by increasing ATF4 expression. Pretreatment of MIN6 cells with the recombinant SCGN partly antagonized ox-LDL-induced ER stress and apoptosis. Furthermore, a co-immunoprecipitation assay revealed an interaction between SCGN and ATF4 in MIN6 cells. Taken together, these results demonstrated that pancreatic β-cell apoptosis induced by ox-LDL treatment can be attributed, in part, to an SCGN/ATF4-dependent ER stress response.